STRATEGI PEMERINTAHAN GIRIREJO DALAM MEWUJUDKAN DESA MANDIRI BUDAYA - Nevia Salsabila Mahanani; Mei Maemunah (Halu Oleo University, 2025)
This study examines the strategy of Kalurahan Girirejo, Imogiri, Bantul, in realising an Independent Cultural Village in accordance with Law No. 13 of 2012 and Yogyakarta Governor Regulation No. 93 of 2020. The research employed a descriptive qualitative method with data collected through interviews, observations, and documentation, analysed using the strategic management framework of Wheelen & Hunger (2003). Kalurahan Girirejo has strong cultural potential, including the heritage of the Mataram Kingdom, traditional arts, keris, batik, and cultural tourism attractions. The development strategy is structured around four main pillars: Cultural Village, Tourism Village, Prima Village, and Preneur Village. The implementation covers cultural preservation, tourism development, women’s empowerment, and support for micro, small, and medium enterprises (MSMEs). Despite challenges such as limited budget, human resources, and competition with other cultural destinations, Kalurahan Girirejo has managed to sustain its programs. Based on the indicators of Governor Regulation No. 93/2020, in 2024, Girirejo obtained accreditation as a Cultural Village. This strategic approach not only safeguards cultural heritage but also strengthens the community’s socio-economic resilience, making it a replicable model for other Independent Cultural Villages in Yogyakarta.